2020
DOI: 10.1177/0194599820944892
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Bilateral Vocal Fold Paralysis in Children: A Systematic Review and Meta‐analysis

Abstract: Objectives To examine and compare the outcomes of various types of glottic widening surgery (GWS) for initial management of bilateral vocal fold paralysis (BVFP) in children, the outcomes of different GWS procedures in children who underwent initial tracheostomy, and the rate of decannulation in children who underwent tracheostomy alone versus tracheostomy followed by GWS. Data Sources PubMed, Web of Science, Cochrane Library, and Embase were searched following the PRISMA guidelines (Preferred Reporting Items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 108 publications
(186 reference statements)
0
15
0
Order By: Relevance
“…The natural history of BVCP depends on its etiology, including trauma, neurologic disorders (e.g., Arnold–Chiari malformation, hydrocephalus, and cerebral palsy), hypoxia, as well as iatrogenic (e.g., related to intubation or surgery) and idiopathic causes. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural history of BVCP depends on its etiology, including trauma, neurologic disorders (e.g., Arnold–Chiari malformation, hydrocephalus, and cerebral palsy), hypoxia, as well as iatrogenic (e.g., related to intubation or surgery) and idiopathic causes. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of BVCP depends on its etiology, including trauma, neurologic disorders (e.g., Arnold-Chiari malformation, hydrocephalus, and cerebral palsy), hypoxia, as well as iatrogenic (e.g., related to intubation or surgery) and idiopathic causes. [24] A retrospective review of idiopathic BVCP cases showed that of the 26 neonates, 19 (73%) underwent endotracheal intubation immediately after birth. Among them, 14 (74%) could not be extubated; therefore, they underwent tracheostomy at a median age of 62 days.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Thorpe and Kanotra examined only paediatric patients (115). They compared the decannulation rates of four different surgical techniques (suture lateralization, cricoid split, arytenoidectomy and cordectomy/ cordotomy).…”
Section: Association Of Surgical Technique To Revision Surgery Ratementioning
confidence: 99%
“…Pediatric bilateral vocal fold dysfunction (BVFD) is a well-documented cause of neonatal respiratory distress and stridor and is typically defined as immobility or hypomobility involving both true vocal folds. 1,2 Among all causes of neonatal stridor, vocal fold dysfunction is the second most common (6%-23%) after laryngomalacia (45%-75%) with reports of bilateral involvement ranging from 30% to 60%. [2][3][4][5] The reported annual incidence of pediatric congenital BVFD is approximately 0.75 per 1,000,000 neonates cases.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 The natural course is influenced by the etiology of BVFD with the most common being congenital idiopathic (58.5%), neuromuscular (27.2%), and iatrogenic (14.2%) based on a recent systematic review. 1 The reported spontaneous recovery rate is highly variable but in general, has been reported between 50% and 65% of patients with BVFD with studies reporting differences in recovery depending on etiology; in general, those with idiopathic BVFD were more likely to spontaneously improve. 2,[7][8][9] The historical gold standard treatment has been early tracheostomy (performed in 57%-100% of cases), although there appears to be a trend favoring conservative surgical management first with glottic widening surgery (cricoid split, arytenoidectomy, suture lateralization, cordectomy, botox) given the psychological, financial, and social disadvantages involved in the management of a tracheostomy.…”
Section: Introductionmentioning
confidence: 99%